Écologie et dynamique spatio-temporelle des mangroves au Togo - Folega Fousseni; Rakotondrasoa Miaratiana Andrianamenoso; Wala Kpérkouma; Woegan Y. Agbelessessi; Kanda Madjouma; Pereki Hodabalo; Polo-Akpisso Aniko; Batawila Komlan; Akpagana Koffi (VertigO)
In Togo, the building of harbor facilities, the construction of the hydroelectric dam plant of Nangbeto, urban growth and activities relating to the installation of fish farms, and the expansion of croplands are the major causes of a drastic degradation of mangroves. For a better management of this ecosystem, assessment of the current structure of mangroves, their spatiotemporal dynamics and socioeconomic issues related to mangroves were performed. Data from forest inventory, structured interviews and Landsat images of 1986 and 2014 were used. Inventories have identified 23 plant species distributed among 23 genera and 17 families dominated by Rhyzophora racemosa and Avicennia germinans. The hierarchical classification of forest inventory samples has identified three groupings of mangrove plants. Investigations show that stakeholders use wood from the mangrove for energy and fuelwood purposes. From 1986 to 2014 the land use/land cover patterns in the study area has undergone tremendous changes. Floodplains and tannes find their areas increased by 39.91 % and 46.06 % respectively, while wooded vegetation cover in whole lost 47.19 % of its area. Anthropogenic pressures would be the main cause of the degradation affecting mangroves ecosystem services and productivity. However, due to the ecological importance of mangroves, there is a need for an appropriate management plan including the contextual realities of mangroves landscapes.